Electron Impact and High Resolution Mass Spectral Studies of 3-Subsituted 7,8-Dimethyl1-2,4,3-benzodioxaphosphephin 3-Oxides - Naga Raju, B.; Prasad, M.V.S. (Asian Journal of Chemistry, 2010)
The electron impact mass spectra of 3-aryloxy/amino-1,5-dihydro-7,8- dimethyl-2,4,3-benzodioxaphosphepin 3-oxides were studied to understand their fragmentation pattern and to establish their structures. 4,5-Dimethylbenzocyclobutane radical cation at m/z 132 is a predominant daughter ion in the title compounds. The fragmentation processes are supported by high resolution mass spectral data.